Gait kinematics analysis of the idiopathic scoliosis patient - Audrey Esteves; Diogo Cunha dos Reis; Eliane Ramos (Universidade Federal de Santa Catarina, 2006)
Idiopathic Scoliosis (IS) is apparent structural deformity of the spine being able to provoke alterations in the gait. Considering these alterations it was intended to describe the kinematics characteristics of the gait in IS patient objectifying to compare the individual in two distinct moments during rehabilitation process. The research individual was a university student with 25 years IS patient developed from infancy. The instrument used for the data collection was the system of three-dimensional reconstruction of movement DMAS 5,0 of the SPICATek®. The results had shown that there is no significant differences for the space/temporal variables when to compare the two collections; with relation to normality was evidenced significant differences for the variables TPD (p=0,015), TPE (p=0,011), TAS-E (p=0,023), CPD (p=0,0000038), CPE (p=0,000014), CPASS (p=0,00090), LP (p=0,049), CAD (p=0,036) and v (p=0,015); when comparing the individual of the research with other referring studies the ISpatients was possible to observe superior values for the variables TAD-D and TAD-E and inferior values for the TBD, TBE, TAS-D, TAS-E, CPD, CPE, CAD and v; with relation to the side asymmetry between the variables TAD-D and TAD-E (p= 0,037) was evidenced in the second collection, and between CPD and CPE in both of them (C1 p=0,016 e C2 p=0,011). For the displayed it can be concluded that the individual presented problems in the gait, possibly caused for the structural deformity present in the column, having presented same differences for the majority of the variables in the comparison with normal individuals. Referring to the period of rehabilitation, between the collections, believes that it did not contribute for possible alterations in the gait. RESUMO A escoliose idiopática (EI) é uma deformidade estrutural aparente da coluna vertebral, podendo provocar alterações na marcha. Considerando essas alterações, procurou-se descrever as características cinemáticas damarcha em um indivíduo portador de EI, visando comparar o sujeito em dois momentos distintos durante processo reabilitativo. O sujeito de pesquisa foi uma estudante universitária com 25 anos, portadora de EI desenvolvida a partir da infância. O instrumento utilizado para a coleta de dados foi o sistema de reconstrução tridimensional de movimento DMAS 5.0, da SPICAtek®. Os resultados mostraram que não houve diferenças significativas para as variáveis espaço-temporais, comparando as duas coletas; com relação a dados de indivíduos normais, constatousediferenças significativas para as variáveis TPD (p=0,015), TPE (p=0,011), TAS-E (p=0,023), CPD (p=0,0000038), CPE (p=0,000014), CPASS (p=0,00090), LP (p=0,049), CAD (p=0,036) e v (p=0,015); ao comparar o sujeito da pesquisa com outros estudos referentes a indivíduos escolióticos, foi possível observar valores superiores para as variáveis TAD-D e TAD-E, e valores inferiores para TBD, TBE, TAS-D, TAS-E, CPD, CPE, CAD e v; com relação à lateralidade, verificou-se assimetria entre as variáveis TAD-D e TAD-E (p= 0,037) na segunda coleta, e entre CPD e CPE em ambas as coletas (C1 p=0,016 e C2 p=0,011). Concluiu-se que o sujeito apresentou comprometimentos na marcha, possivelmente ocasionados pela deformidade estrutural presente na coluna, tendo o mesmo apresentado diferenças para a maioria das variáveis na comparação com indivíduos normais. Quanto ao período de reabilitação,entre as coletas, acredita-se que este não contribuiu para possíveis alterações na marcha.